Switchmode power supply handbook - Billings, Keith H. (McGraw-Hill Professional, 2011)
"The definitive guide to switchmode power supply design--fully updatedCovering the latest developments and techniques, Switchmode Power Supply Handbook, third edition is a thorough revision of the industry-leading resource for power supply designers. New design methods required for powering small, high-performance electronic devices are presented. Based on the authors' decades of experience, the book is filled with real-world solutions and many nomograms, and features simplified theory and mathematical analysis.This comprehensive volume explains common requirements for direct operation from the AC line supply and discusses design, theory, and practice. Engineering requirements of switchmode systems and recommendations for active power factor correction are included. This practical guide provides you with a working knowledge of the latest topologies along with step-by-step approaches to component decisions to achieve reliable and cost-effective power supply designs.Switchmode Power Supply Handbook, third edition covers: Functional requirements of direct off-line switchmode power supplies Power components selection and transformer designs for converter circuits Transformer, choke, and thermal design Input filters, RFI control, snubber circuits, and auxiliary systems Active power factor correction system design Worked examples of would components Examples of fully resonant and quasi-resonant systems A resonant inverter fluorescent ballast An example of high-power phase shift modulated system A new MOSFET resonant inverter drive scheme A single-control, wide-range wave oscillator "